BUSINESS ACTORS' RESPONSIBILITIES TOWARDS CONSUMERS FOR EXPIRED PRODUCTS IN SUPERMARKETS - Elis Herlina; Dini Fitriani Komalasari (JILPR Journal Indonesia Law and Policy Review, 2024)
The existence of expired food products has become a problem among the general public, because expired food products are no longer suitable for consumption because of the risk of poisoning for people who consume them. The purpose of this study is to determine and examine the responsibility of business actors towards consumers for expired products in supermarkets in connection with Law Number 8 of 1999 concerning Consumer Protection. The research method in writing this thesis is descriptive analysis, carried out with a normative juridical approach method, namely a normative legal writing method. Data collection techniques in the form of library research using 3 legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. The results showed that business actors who violate provisions related to expired food products, such as not clearly stating the expiration date, may be subject to administrative sanctions or other legal sanctions in accordance with applicable regulations. Based on Article 19 paragraph (1) of the Consumer Protection Law, the responsibility of business actors includes compensation for damage, pollution and consumer losses. The government is expected to provide direction and guidance to business actors regarding the importance of including expiration dates to ensure the safety of products being traded.